Los ficheros de datos RAI y ASNEF: problemática, regulación y perspectivas - Graciano Regalado, Juan Carlos (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2004)
This paper describes Spanish regulation of agencies and credit reference files, especially RAI and ASNEF. How to access information, rectify or destroy wrong information, in order to use law to protect citizen’s rights.
Keywords: Credit reference file; Data protection office; Data protection law; Credit reparting bureau RAI; Credit reparting bureau ASNEF; RAI File; ASNEF File; Interbank teamwark